Analysis of class I complexity induced spherical polytropic models for compact objects - Malik, Adnan; Mardan, S. A.; Naz, Tayyaba; Khan, Shiraz (Frontiers in Astronomy and Space Sciences, 2023)
In this research, we present a comprehensive framework that utilizes a complexity factor to analyze class $I$ generalized relativistic polytropes. We establish class $I$ generalized Lane-Emden equations using the Karmarkar condition under both isothermal and non-isothermal regimes. Our approach considers a spherically symmetric fluid distribution for two cases of generalized polytropic equation of state: $(i)$ the mass density case $μ_{o}$ and $(ii)$ the energy density case $μ$. To obtain numerical solutions for both cases, we solve two sets of differential equations that incorporate the complexity factor. Finally, we conduct a graphical analysis of these solutions.